Incidence and impact of venous thromboembolism in hospitalized patients with Crohn-disease. (3rd October 2022) - Keller, K; Sivanathan, V; Schmitt, V H; Ostad, M A; Munzel, T; Espinola-Klein, C; Hobohm, L
Abstract: Background: Prevalence of Crohn's disease (CD) is high in North America and in Europe ranging between 100 and 350 patient-cases per 100, 000 citizens. CD is characterized by chronic inflammation with a progressive course and is often associated with different intestinal as well as extra-intestinal complications. CD is associated with both, other inflammatory diseases such as ankylosing spondylitis and psoriasis as well as venous thromboembolism (VTE). CD causes an activation of coagulation system, which might be the main reason for an increased risk of thromboembolic complications. Beside previous study results regarding higher VTE risk of patients with CD in comparison to the general population, particularly, data on impact of VTE on survival and risk factors for the occurrence of VTE in CD are sparse. Purpose: The objectives of our study were to provide evidence about the current and past prevalence of VTE events in hospitalized patients with CD and to investigate the impact of VTE on outcomes of CD patients. Methods: The German nationwide inpatient sample was screened for patients admitted due to CD (ICD-code K50) (source: RDC of the Federal Statistical Office and the Statistical Offices of the federal states, DRG Statistics 2005–2018, own calculations). CD hospitalizations were stratified for VTE and risk factors for VTE and impact of VTE on in-hospital case-fatality rate were investigated. Results: Overall, 333, 975 patients-cases with hospital admissions due to CD were counted in Germany (median age 38.0 [IQR 24.0–52.0] years, 56.0% females) during the observational period between 2005 and 2018. VTE rate increased slightly from 0.6% to 0.7% (β 0.000097 [95% CI 0.000027 to 0.000167], P=0.007) from 2005 to 2018 and with age-decade of life (β 0.0017 [95% CI 0.0016 to 0.0019], P<0.001). In total, 0.7% (n=2, 295) of the CD inpatients had an event of VTE. Patients with VTE were in median 12 years older (49.0 [34.0–62.0] vs. 37.0 [24.0–52.0] years, P<0.001) and CD colon-manifestations were more prevalent in those patients (32.0% vs. 27.7%, P<0.001). Age ≥70 years, obesity, colon-involvement, cancer, surgery, thrombophilia, and heart failure were strongly associated with higher risk of VTE in CD patients. In-hospital death occurred 15-times more often in CD with VTE than without (4.5% vs. 0.3%, P<0.001). VTE was independently associated with substantially increased in-hospital case-fatality rate (OR 9.31 [95% CI 7.54–11.50], P<0.001). Conclusions: VTE is a life-threatening event in hospitalized CD patients associated with 9.3-fold increased case-fatality rate. Older age, obesity, colon involvement, cancer, surgery, thrombophilia and heart failure were strong risk factors for VTE in patients with CD. Funding Acknowledgement: Type of funding sources: None.